2018
DOI: 10.1002/jcph.1301
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Atorvastatin on Cardiometabolic Risk Factors in Young Women With and Without Hyperprolactinemia

Abstract: Long-term prolactin excess is often accompanied by numerous metabolic complications. No previous study has compared the effect of statin therapy on circulating levels of cardiometabolic risk factors in patients with elevated and normal prolactin levels. The study population consisted of 3 age-, weight-, and lipid-matched groups of young women: 19 women with untreated hyperprolactinemia (group A), 20 normoprolactinemic women receiving bromocriptine treatment (because of previous hyperprolactinemia) (group B), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Unfavorable changes in cardiometabolic risk factors induced by prolactin excess were reversed by dopaminergic agents, particularly by cabergoline [21]. Finally, the impact of hypolipidemic agents on cardiometabolic risk factors did not differ between patients with monomeric hyperprolactinemia effectively treated with dopamine agonists and subjects in whom prolactin levels were within the reference range [19,20].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Unfavorable changes in cardiometabolic risk factors induced by prolactin excess were reversed by dopaminergic agents, particularly by cabergoline [21]. Finally, the impact of hypolipidemic agents on cardiometabolic risk factors did not differ between patients with monomeric hyperprolactinemia effectively treated with dopamine agonists and subjects in whom prolactin levels were within the reference range [19,20].…”
Section: Introductionmentioning
confidence: 91%
“…Monomeric hyperprolactinemia make subjects more susceptible to the development of insulin resistance, prediabetes, atherogenic dyslipidemia, weight gain, subclinical atherosclerosis and endothelial dysfunction [12][13][14][15][16][17][18]. Moreover, untreated monomeric hyperprolactinemia in dyslipidemic subjects exerted a negative impact on cardiometabolic effects of atorvastatin [19] and fenofibrate [20]. Unfavorable changes in cardiometabolic risk factors induced by prolactin excess were reversed by dopaminergic agents, particularly by cabergoline [21].…”
Section: Introductionmentioning
confidence: 99%
“…Dopamine agonists, the drugs of choice in the treatment of monomeric hyperprolactinaemia, reduced plasma levels of cardiometabolic risk factors [14]. Moreover, cardiometabolic effects of atorvastatin [15] and fenofibrate [16] depended on the prolactin status of patients, being much less pronounced (or even absent) in women with untreated hyperprolactinaemia than in women with bromocriptine-treated hyperprolactinaemia and drug-naïve women with normal prolactin levels. These results suggest that the presence of elevated levels of monomeric prolactin eliminates the beneficial effect of atorvastatin on plasma levels of cardiometabolic risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…These pleiotropic effects partially explain why fibrate treatment may bring cardiovascular benefits, which are observed mainly in subjects with atherogenic dyslipidaemia 4,5 . Unfortunately, some endocrine disorders may negatively affect extra‐lipid properties of hypolipidaemic agents 6‐11 . Previous studies showed that pleiotropic effects of fenofibrate were attenuated by thyroid hypofunction, 9 elevated levels of monomeric prolactin 10 and macroprolactinemia, 11 despite the fact that these studies included only patients with mild or moderate forms of these disorders (for ethical reasons subjects with overt hypothyroidism and severe prolactin excess were excluded).…”
Section: Introductionmentioning
confidence: 99%